Pre-lithiated diaphragm as well as preparation method and application thereof
By applying sustained release lithium supplement agent on the prelithiated separator of lithium-ion batteries, using the dissociation and release mechanism of nitrate, the problems of irreversible lithium loss and poor stability of lithium supplement agent in lithium-ion batteries are solved, and the circulation of the battery is improved Performance and energy density.
Patent Information
- Application Number
- CN202411284955.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
AI Technical Summary
Lithium-ion batteries have irreversible lithium loss problems during the first cycle, especially the loss of silicon-based materials, and the existing pre-lithiation technology has problems such as poor stability and poor conductivity of lithium supplement additives, which affects the battery cycle life and energy. Increased density.
A prelithiated diaphragm is adopted, including a substrate and a sustained-release preliminary agent coating coated on the positive electrode side. The sustained-release lithium supplement is composed of nitrates coated on the outer layer of the lithium supplement agent, and is dissolved by nitrate. Release lithium supplement agent to form a stable protective SEI film and lithium metal alloy, and continuously supplement lithium loss during the cycle.
It effectively improves the cycling performance and energy density of the battery, maintains a high lithium ion concentration, extends the cycle life of the battery, and improves the cycling performance while ensuring that the battery cell performance does not decrease.
Smart Images

Figure BDA0005042855710000031 
Figure BDA0005042855710000051 
Figure FDA0005042855700000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a pre-lithiation diaphragm and a preparation method and application thereof. Background Art
[0002] Since its invention, lithium-ion batteries have greatly changed people's lives. The rapid development of electric vehicles, grid energy storage, and portable electronic devices has made the research and development of higher energy density lithium batteries more urgent. The negative electrode material of lithium batteries is currently mainly graphite, which has advantages such as high conductivity and high stability, but is close to the theoretical specific capacity. The improvement of battery energy density drives the negative electrode to high performance iteration. The theoretical specific capacity of silicon-based negative electrodes is high, but there are problems such as volume expansion, poor conductivity, and unstable SEI film, and they are mostly used with graphite doping.
[0003] In the first cycle of lithium-ion batteries, the SEI film formed on the surface of the graphite negative electrode has an initial irreversible capacity loss of 5-15%, and the high-capacity silicon-based material has a loss of 15-35%. Pre-lithiation of electrode materials to supplement irreversible lithium loss is one of the important means to solve the problem of large irreversible lithium loss in silicon-based materials. Currently, the commonly used pre-lithiation technologies are mainly divided into negative electrode pre-lithiation and positive electrode pre-lithiation. Negative electrode pre-lithiation is to introduce active lithium into the negative electrode to compensate for its capacity loss caused by SEI growth. There are mainly chemical methods, electrochemical methods and other technical routes, but the negative electrode pre-lithiation is in direct contact with metallic lithium, which is incompatible with existing battery production lines and has high transformation costs. Positive electrode pre-lithiation is to add active lithium to the positive electrode in advance to release lithium ions to the negative electrode and supplement the irreversible capacity during the first charge and discharge process. The main methods include additives and over-lithiation positive electrode materials. The process is simple, the cost is low, and it can be added directly during the homogenization process of the positive electrode slurry without additional process improvements. However, positive electrode lithium supplement additives generally have poor stability and are easy to react with carbon dioxide and water in the air. In addition, the decomposition potential is relatively high. It is necessary to charge the voltage to a higher potential during the first cycle of charging to release its capacity and exert the lithium supplement effect of the lithium supplement agent. In response to the poor stability and conductivity of lithium supplement additives, the CN115000536A patent coats the surface of the additive with a semi-finished carbon layer containing hydroxyl groups. This coating layer can act as a separator for water and carbon dioxide in the air, and the semi-finished carbon layer containing hydroxyl groups has a partial conductivity function, which can improve the conductivity of the positive electrode lithium supplement material.
[0004] Although pre-lithiation has been shown to effectively compensate for the irreversible lithium loss during the SEI film formation stage by introducing additional active lithium into the battery, it ignores the continuous lithium consumption that occurs during the entire cycle. Controllable long-term lithium replenishment has a more profound effect on improving the cycle life of lithium batteries.
[0005] At present, there are also some patents for long-term lithium supplementation and slow-release lithium supplementation. For example, Chinese patent CN114284463A sets diaphragms on both sides of the lithium-containing metal body. The lithium-containing metal body is a whole piece structure, and the diaphragms on both sides are provided with openings. The part of the lithium-containing metal body not covered by the diaphragm forms the first-effect lithium supplementation area, and the part covered by the diaphragm forms the slow-release lithium supplementation area. However, this method has a complex production process and is not conducive to mass production and application. Another example is Chinese patent CN117117357A, which coats silazane, siloxane, sulfonic acid silane or carbodiimide compounds on the surface of the lithium supplement agent, mixes with the positive electrode slurry and coats it on the current collector. During the charge and discharge cycle of the battery, the water and acidic substances in the battery are consumed, and lithium ions are slowly released to achieve a long-term lithium supplementation effect. However, another problem with positive electrode lithium supplementation is that it will reduce the mass proportion of active substances, which is not conducive to the improvement of battery energy density. Summary of the invention
[0006] The purpose of the present invention is to provide a pre-lithiation diaphragm for replenishing irreversible lithium loss in the first cycle of a lithium-ion battery; another purpose of the present invention is to provide a method for preparing the pre-lithiation diaphragm; another purpose of the present invention is to provide an application of the pre-lithiation diaphragm.
[0007] The present invention provides a pre-lithiation diaphragm, comprising a substrate and a slow-release pre-lithium agent coating coated on the positive electrode side of the substrate, wherein the slow-release pre-lithium agent coating comprises a slow-release lithium supplement agent, and the slow-release lithium supplement agent comprises a lithium supplement agent and a slow-release agent coated on the outer layer of the lithium supplement agent.
[0008] Furthermore, the thickness of the sustained-release pre-lithium agent coating is 1-5 μm; the lithium supplement agent is selected from lithium oxide, lithium sulfide, lithium zirconate, lithium titanate, lithium ferrite, lithium nickelate, lithium oxalate, lithium silicate, Li 2 S / Co composite, Li 2 At least one of the O / Co composites.
[0009] Furthermore, the sustained-release agent is selected from one of magnesium nitrate, copper nitrate and sodium nitrate.
[0010] The surface of the lithium supplement is coated with nitrate to improve the air stability of the lithium supplement. When the battery is working, the nitrate will dissociate into metal ions and nitrate ions in the electrolyte, thereby releasing the coated lithium supplement. The free metal ions will be reduced by metallic lithium to form lithium metal alloys, and the nitrate ions can form a stable protective SEI film on the surface of the negative electrode. The released lithium supplement can replenish the continuous lithium loss that occurs during the cycle. Due to the continuous release of nitrates, the negative electrode will always form a protective SEI layer and a lithium metal alloy, and the battery system can maintain a high lithium ion concentration, thereby improving the battery's cycle performance.
[0011] Furthermore, the preparation method of the sustained-release lithium supplement is as follows: the sustained-release agent is dissolved in an organic solvent to prepare a solution, the solution is evenly sprayed on the surface of the lithium supplement, and after the solvent evaporates, a layer of sustained-release agent is deposited on the surface of the lithium supplement.
[0012] The sustained-release agent is coated on the surface of the lithium supplement.
[0013] Furthermore, the mass ratio of the lithium supplement agent to the sustained-release agent is 2:1-1:30; and the organic solvent is selected from at least one of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), acetone, methanol, and ethanol.
[0014] Furthermore, the substrate is selected from one of polyethylene (PE), polypropylene (PP), polyethylene-polypropylene (PE / PP) composite film, polyethylene terephthalate (PET), polyimide (PI), aramid, and cellulose separator.
[0015] Furthermore, the substrate includes a single-sided or double-sided ceramic coating.
[0016] The present invention also provides a method for preparing a pre-lithiation separator, comprising the following steps:
[0017] S1. Preparing a slow-release pre-lithium agent coating slurry: dispersing a slow-release lithium supplement agent, a binder, and a dispersant in an organic solvent and mixing them evenly;
[0018] S2: coating a slow-release pre-lithiation agent coating slurry: coating the slow-release pre-lithiation agent coating slurry prepared in step S1 on the positive electrode side of the substrate to obtain the pre-lithiation separator as described above.
[0019] Furthermore, in step S1, the raw materials of the sustained-release pre-lithium agent slurry include, by mass percentage:
[0020]
[0021] Furthermore, the binder is selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinylidene fluoride hexafluoropropylene copolymer (PVDF-HFP); the stabilizer is sodium hydroxymethyl cellulose or polyamide wax; and the dispersant is selected from at least one of polyacrylamide and sodium fatty alcohol ether sulfate.
[0022] The present invention also discloses a lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a pre-lithiation separator obtained by the preparation method described above, wherein the lithium ion battery has a capacity retention rate greater than 93% after 1200 cycles at room temperature.
[0023] The present invention discloses a pre-lithiation diaphragm, in which a slow-release lithium supplement is coated on the surface of the diaphragm. Due to the continuous release characteristics of the buffer, the negative electrode will always form a protective SEI layer and a lithium metal alloy, and the battery system can maintain a high lithium ion concentration, thereby improving the battery's cycle performance. In addition, the slow-release lithium supplement is coated on the surface of the diaphragm, and the process is mature, which will not reduce the proportion of active substances on the electrode surface, and therefore will not affect the battery energy density, and can improve the cycle performance while ensuring that the performance of the battery cell is not reduced. DETAILED DESCRIPTION
[0024] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0025] Example 1
[0026] Preparation of sustained-release lithium supplement: The mass ratio of lithium oxide to magnesium nitrate is 1:5. Magnesium nitrate is dissolved in methanol solution and sprayed evenly on the surface of lithium oxide. The mixture is allowed to stand at room temperature or dried in an oven to allow the methanol to evaporate completely. After at least 5 rounds of spraying and drying, the sustained-release lithium supplement is obtained until the magnesium nitrate solution is completely sprayed.
[0027] Preparation of pre-lithiation separator:
[0028] S1 Preparation of sustained-release pre-lithium agent coating slurry: 30 g of sustained-release lithium supplement agent, 1.5 g of PVDF, 0.35 g of sodium hydroxymethyl cellulose and 0.15 g of polyacrylamide are dispersed in 68 g of NMP and stirred evenly.
[0029] S2: coating the slow-release pre-lithium agent coating slurry: coating the slow-release pre-lithium agent slurry prepared in step S1 on the surface of the polyethylene base film by spraying, and after the organic solvent evaporates, the coating thickness is 2 μm.
[0030] Example 2
[0031] The difference between this embodiment and embodiment 1 is that "lithium oxide" is replaced by "lithium ferrite".
[0032] Preparation of sustained-release lithium supplement: The mass ratio of lithium ferrite to magnesium nitrate is 1:5. Magnesium nitrate is dissolved in methanol solution and sprayed evenly on the surface of lithium ferrite. The mixture is allowed to stand at room temperature or dried in an oven to completely evaporate the methanol. After at least 5 rounds of spraying and drying, the sustained-release lithium supplement is obtained until the magnesium nitrate solution is completely sprayed.
[0033] Preparation of pre-lithiation separator:
[0034] S1 Preparation of sustained-release pre-lithium agent coating slurry: 30 g of sustained-release lithium supplement agent, 1.5 g of PVDF, 0.35 g of sodium hydroxymethyl cellulose and 0.15 g of polyacrylamide are dispersed in 68 g of NMP and stirred evenly.
[0035] S2: coating the slow-release pre-lithium agent coating slurry: coating the slow-release pre-lithium agent slurry prepared in step S1 on the surface of the polyethylene base film by spraying, and after the organic solvent evaporates, the coating thickness is 2 μm.
[0036] Example 3
[0037] The difference between this embodiment and embodiment 1 is that "magnesium nitrate" is replaced by "copper nitrate".
[0038] Preparation of sustained-release lithium supplement: The mass ratio of lithium oxide to copper nitrate is 1:5. Copper nitrate is dissolved in methanol solution and sprayed evenly on the surface of lithium oxide. The mixture is allowed to stand at room temperature or dried in an oven to allow the methanol to evaporate completely. After at least 5 rounds of spraying and drying, the sustained-release lithium supplement is obtained until the magnesium nitrate solution is completely sprayed.
[0039] Preparation of pre-lithiation separator:
[0040] S1 Preparation of sustained-release pre-lithium agent coating slurry: 30 g of sustained-release lithium supplement agent, 1.5 g of PVDF, 0.35 g of sodium hydroxymethyl cellulose and 0.15 g of polyacrylamide are dispersed in 68 g of NMP and stirred evenly.
[0041] S2: coating the slow-release pre-lithium agent coating slurry: coating the slow-release pre-lithium agent slurry prepared in step S1 on the surface of the polyethylene base film by spraying, and after the organic solvent evaporates, the coating thickness is 2 μm.
[0042] Example 4
[0043] The difference between this embodiment and embodiment 1 is that the "mass ratio of lithium oxide to magnesium nitrate is 1:5" is replaced by "mass ratio of lithium oxide to magnesium nitrate is 1:15".
[0044] Preparation of sustained-release lithium supplement: The mass ratio of lithium oxide to magnesium nitrate is 1:15. Magnesium nitrate is dissolved in methanol solution and sprayed evenly on the surface of lithium oxide. The solution is left standing at room temperature or dried in an oven to completely evaporate the methanol. After at least 5 rounds of spraying and drying, the sustained-release lithium supplement is obtained after drying.
[0045] Preparation of pre-lithiation separator:
[0046] S1 Preparation of sustained-release pre-lithium agent coating slurry: 30 g of sustained-release lithium supplement agent, 1.5 g of PVDF, 0.35 g of sodium hydroxymethyl cellulose and 0.15 g of polyacrylamide are dispersed in 68 g of NMP and stirred evenly.
[0047] S2: coating the slow-release pre-lithium agent coating slurry: coating the slow-release pre-lithium agent slurry prepared in step S1 on the surface of the polyethylene base film by spraying, and after the organic solvent evaporates, the coating thickness is 2 μm.
[0048] Comparative Example 1
[0049] The difference between this comparative example and Example 1 is that the lithium supplement is not treated with a sustained-release agent.
[0050] (1) Preparation of pre-lithium agent slurry: 5 g lithium oxide, 1.5 g PVDF, 0.35 g sodium hydroxymethyl cellulose and 0.15 g polyacrylamide were dispersed in 93 g NMP and stirred evenly.
[0051] (2) Preparation of lithium supplementing agent diaphragm: The lithium supplementing agent slurry prepared in step 2 is coated on the surface of the polyethylene base film by spraying. After the organic solvent evaporates, the coating thickness is 2 μm.
[0052] Comparative Example 2
[0053] Conventional 2μm ceramic coated polyethylene separator.
[0054] Performance Testing:
[0055] The diaphragms obtained in Examples 1-4 and Comparative Examples 1-2 were assembled into small soft-pack batteries with a ternary positive electrode, a silicon-carbon negative electrode, and an electrolyte. The assembled batteries were pre-charged and subjected to normal temperature cycle (+1C / -1C, 25°C) data analysis. The results are shown in Table 1 below.
[0056] Table 1 Performance test results of lithium-ion batteries assembled from Examples 1-4 and Comparative Examples 1-2
[0057]
[0058] As can be seen from Table 1, compared with the conventional ceramic-coated diaphragm of Comparative Example 2, the first charging capacity of the diaphragms of Comparative Example 1 and Examples 1-4 is significantly improved, thanks to the higher specific energy of the lithium supplement agent. Due to the large irreversible capacity of the lithium supplement agent, the first discharge capacity is not greatly improved, and the first coulomb efficiency is slightly reduced. By comparing the room temperature cycle capacity retention data of Comparative Example 1 and Comparative Example 2, it is found that the difference between the two is not large, indicating that the lithium supplement agent without a sustained release agent coating only effectively compensates for the irreversible lithium loss in the SEI film formation stage, and has little effect on the continuous lithium consumption that occurs during the entire cycle. Compared with Comparative Example 2, the capacity of the battery cell in Examples 1-4 is greatly improved, because the lithium supplement agent also has capacity to play. Compared with the ordinary lithium supplement layer diaphragm, that is, Comparative Example 1, the capacity retention rate of the entire cycle process is greatly improved. Not only is the capacity of the battery cell greatly improved, but the entire cycle process is also significantly improved. The capacity retention rate of 1200 cycles of room temperature cycles remains above 93%.
[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A pre-lithiation separator, characterized in that: It comprises a substrate and a slow-release pre-lithium agent coating coated on the positive electrode side of the substrate, wherein the slow-release pre-lithium agent coating comprises a slow-release lithium supplement agent, and the slow-release lithium supplement agent comprises a lithium supplement agent and a slow-release agent coated on the outer layer of the lithium supplement agent.
2. A pre-lithiation separator according to claim 1, characterized in that: The thickness of the sustained-release pre-lithium agent coating is 1-5 μm; the lithium supplement agent is selected from at least one of lithium oxide, lithium sulfide, lithium zirconate, lithium titanate, lithium ferrite, lithium nickelate, lithium oxalate, lithium silicate, Li2S / Co complex, and Li2O / Co complex; the sustained-release agent is selected from one of magnesium nitrate, copper nitrate, and sodium nitrate.
3. A pre-lithiation separator according to claim 1, characterized in that: The preparation method of the sustained-release lithium supplement is as follows: dissolving the sustained-release agent in an organic solvent to prepare a solution, spraying the solution on the surface of the lithium supplement, and depositing a layer of the sustained-release agent on the surface of the lithium supplement after the solvent evaporates.
4. A pre-lithiation separator according to claim 3, characterized in that: The mass ratio of the lithium supplement agent to the sustained-release agent is 2:1-1:30; the organic solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, acetone, methanol and ethanol.
5. A pre-lithiation separator according to claim 1, characterized in that: The substrate is selected from one of polyethylene, polypropylene, polyethylene-polypropylene composite film, polyethylene terephthalate, polyimide, aramid, and cellulose separator.
6. A pre-lithiation separator according to claim 5, characterized in that: The substrate includes a single-sided or double-sided ceramic coating.
7. A method for preparing a pre-lithiation separator, characterized in that: The following steps are involved: S1. Preparing a slow-release pre-lithium agent coating slurry: dispersing a slow-release lithium supplement agent, a binder, and a dispersant in an organic solvent and mixing them evenly; S2 coating a slow-release pre-lithiation agent coating slurry: coating the slow-release pre-lithiation agent coating slurry prepared in step S1 on the positive electrode side of the substrate to obtain a pre-lithiation separator as described in any one of claims 1-6.
8. The method for preparing a pre-lithiation separator according to claim 7, characterized in that: In the step S1, the raw materials of the sustained-release pre-lithium agent slurry include, by mass percentage:
9. The method for preparing a pre-lithiation separator according to claim 8, characterized in that: The binder is selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene, and polyvinylidene fluoride hexafluoropropylene copolymer; the stabilizer is sodium hydroxymethyl cellulose or polyamide wax; and the dispersant is selected from at least one of polyacrylamide and sodium fatty alcohol ether sulfate.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, an electrolyte and a pre-lithiation separator obtained by the preparation method according to any one of claims 7 to 9. The lithium-ion battery has a capacity retention rate of more than 93% after 1200 cycles at room temperature.
Citation Information
Cited By
Negative-electrode-free sodium metal battery electrolyte as well as preparation method and application thereof
CN119852566A
Functional material for diaphragm, preparation method of functional material, diaphragm and lithium ion battery
CN121367025A
Functional material for diaphragm, preparation method thereof, diaphragm and lithium ion battery
CN121367025B